Catalytic methanotreating of vegetable oil: A pathway to Second-generation biodiesel. (1st March 2022) - Li, Yimeng; Xu, Hao; Li, Zhaofei; Meng, Shijun; Song, Hua
Graphical abstract: A so-called methanotreating process is successfully developed for upgrading vegetable oils to renewable diesel with significantly improved quality in terms of composition and distillation feature. Highlights: Methane has a positive effect on catalytic cracking of vegetable oil. Remarkable oxygen reduction has been achieved by using Ga-Ce/TS-1 catalyst. Significant light fraction yield has been obtained by using Ga-Ce/TS-1 catalyst. Methane presence decreases olefin yield and coke yield. Abstract: Vegetable oil is one of the most commonly used feedstocks for the production of biodiesel, while the first-generation biodiesel suffers from the disadvantages of considerable instability and corrosivity. Developing second-generation biodiesel is momentous for the sustainable development of global energy, which overcomes the shortcomings of first-generation biodiesel. The methanotreating of vegetable oil is a potential new route for the production of second-generation biodiesel, which is comprehensively investigated in this study. Throughout the screening of the catalysts, Ga-Ce/TS-1 demonstrates the best overall performances in this methane-incorporated process, leading to 84.23 % of liquid yield, 0.95 % of methane conversion, 72.8 % of oxygen content reduction, and 71% of light hydrocarbon distillates yield. The participation of methane promotes deoxygenation performance, optimizes the composition of paraffinic and olefinic hydrocarbons, as well as suppresses coke formation. The catalytic methanotreating of vegetable oil is confirmed to be a promising pathway to second-generation biodiesel.